2018
DOI: 10.15671/hjbc.2018.220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Cytotoxicity of Melia azedarach L. Extracts on Human Adipose-derived Mesenchymal Stem Cells

Abstract: Ö Z B u çalışmada, Melia azedarach L. yeşil meyve ve yapraklarının sulu özleri iki farklı özütleme yöntemi kullanılarak elde edildi. Yeşil meyve ve yaprakların özütleme verimleri sırasıyla, demleme yöntemi için %24.11 ve %37.98; çalkalama yöntemi için ise %17.76 ve %27.00 olarak bulundu. Demleme yöntemi ile ilgili toplam fenolik içerik, yeşil meyve özü için 173.67±10.84 mg galik asit eşdeğeri (GAE)/g kuru ağırlık ve yaprak özü için 312.33±9.81 mg GAE/g kuru ağırlık cinsinden tespit edildi. Diğer yandan demleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The present study reports the antioxidant activity levels of Salvadora persica extracts in terms of mg Trolox/L for the first time in the literature. When comparing the results with another study published by our group (21), we concluded that a sufficient antioxidant capacity was achieved in Method II.…”
Section: Thesupporting
confidence: 52%
See 2 more Smart Citations
“…The present study reports the antioxidant activity levels of Salvadora persica extracts in terms of mg Trolox/L for the first time in the literature. When comparing the results with another study published by our group (21), we concluded that a sufficient antioxidant capacity was achieved in Method II.…”
Section: Thesupporting
confidence: 52%
“…In order to identify the chemical composition of miswak extracts, the GC-MS analysis was conducted according to our previous study (21). Initially, lyophilized miswak extracts were dissolved in Milli-Q water and filtered through a 0.22 µm sterile filter.…”
Section: Gas Chromatography-mass Spectroscopy Analysis Of Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…After confirming the absence of cytotoxic effect in human adipose mesenchymal stem cells (hAd-MSCs, Figure S53), and the evaluation of their drug-like parameters (Table S4), peptidomimetics 4a and 6a were studied in the human SH-SY5Y neuroblastoma cell line. This cell line is widely acknowledged as an in vitro model in PD research and is also a good model to determine neurotoxicity .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of nonspecific cytotoxicity during early drug development, the target compounds 2­(a-d) were screened in vitro for cytotoxicity on human adipose mesenchymal stem cells (hAd-MSCs), as previously reported. , In this assay, cell viability is estimated based on the ability of viable cells to reduce the tetrazolium compound 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2 H -tetrazolium, inner salt (MTS), into the corresponding formazan derivative by functional mitochondrial enzymes . The cytotoxicity results obtained from the MTS assay on hAd-MSC cells are depicted in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%